Strategi Peningkatan Kinerja Karyawan PT. Ciptaunggul Karya Abadi dengan Metode Analytical Hierarchy Process - Waliyyu, Rafi Umar; Fitriani, Risma (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
In determining alternative decisions for improving its employee performance, PT. Cipta Karya Abadi appraises its employee performance with the help of predetermined criteria limits. To find out the level of quality of employees, work facilities, employee welfare which is a priority in performance improvement strategies so that employees get comfortable and motivated and can reduce feelings of boredom when carrying out work, can be conducted by looking at some of the problems that occur in the company. This research was conducted to find out strategies that can be used to increase employee performance in making a company organization more efficient. Based on the results described in the results and discussion, it can be concluded that the criteria used as a reference in employee performance improvement strategies are additional tasks, management skills, work skills, and communication skills. From the above criteria, several alternatives proposed by the company to improve employee performance. They are HR Quality Improvement, Work Facilities Improvement and Welfare Improvement. The three calculations that have been carried out using the Analytical Hierarchy Process (AHP) method to determine employee performance improvement strategies show that the first alternative priority is to increase work facilities with a priority value of 0.3448, then the second and third alternatives are to improve the quality of human resources and increase welfare by the same priority value of 0.3276.